Bond Strength of Composite Resin to Pulp Capping Biomaterials after Application of Three Different Bonding Systems - Zahra Jaberi-Ansari; Maryam Mehdilou; Maryam Ahmadyar; Saeed Asgary (Tabriz University of Medical Sciences, 2013)
Background and aims. Bonding of composite resin filling materials to pulp protecting agents produces an adhesive joint which is important for the quality of filling as well as success of restoration. We aimed to assess the bond strength of composite resin to three pulp capping biomaterials: Pro Root mineral trioxide aggregate (PMTA), Root MTA (RMTA) and calcium enriched mixture (CEM) cement, using three bonding systems [a total-etch (Single Bond) and two self-etch systems (Protect bond and SE Bond)]. Materials and methods. Ninety acrylic molds, each containing a 6×2-mm hole, were divided into 3 groups and filled with PMTA, RMTA and CEM cements. The samples in each experimental group were then randomly divided into 3 subgroups; Single Bond, Protect Bond and SE Bond bonding systems were applied to the tested materials. Cylindrical forms of composite resin (Z100, 2×2 mm) were placed onto the samples and cured. Shear bond strength values were measured for 9 subgroups using a universal testing machine. Data were analyzed using two-way ANOVA. Results. The average shear bond strengths of Z100 composite resin after application of Single Bond, Protect Bond and SE Bond systems were as follows; PMTA: 5.1±2.42, 4.56±1.96 and 4.52±1.7; RMTA: 4.71±1.77, 4.31±0.56 and 4.79±1.88; and CEM cement: 4.75±1.1, 4.54±1.59 and 4.64±1.78 MPa, respectively. The type of pulp capping material, bonding system and their interacting effects did not have a significant effect on the bond strengths of composite resin to pulp capping biomaterials. Conclusion. Within the limitations of this in vitro study, bond strength of composite resin to two types of MTA as well as CEM cement were similar following application of the total-etch or self-etch bonding systems.